Determination of Sodium, Potassium, Calcium, Magnesium and Ammonium in Tobacco by Ion Chromatography - Hu, Qiufen; Xu, Yiran; Ye, Yanqing; Li, Yinke; Yang, Guangyu (Asian Journal of Chemistry, 2010)
A new method for the determination of sodium, potassium, calcium, magnesium and ammonium in tobacco by ion chromatography and sample preparation with matrix solid phase dispersion has been developed. The tobacco sample and C18 (1:4) were homogenized in a mortar and then packed into a cartridge. The sodium, potassium, calcium, magnesium and ammonium were eluted from the cartridge with 1.0 % hydrochloric acid and they were separated on an Ionpac® CS 16 (5.0 × 250 mm, 5 μm) cation ion exchange column with 0.03 mol/L methane sulfonic acid as mobile phase. The standard recoveries were in the range of 94-104 %. The relative standard deviations were less than 2.6 % (intra-day) and 3.3 % (inter-day). Results are satisfactory.